THE ABORIGINES’ INTERCONNECTIVITY WITH NATURE AND SENSE OF BELONGINGTO THE LAND AS SEEN IN KIM SCOTT’S THAT DEADMAN DANCE (International Journal of Food and Nutritional Sciences, 2022)
Humanbeings have a natural affinity for nature. In this world everything is interconnected -- people,plants,animals,land forms and celestial bodies. This article reviews the interconnectivity between nature and the Aborigines. Land means different things to Aboriginesand non-Aborigines.Aborigines have spritual,physical,social and cultural connection towards their land. They give vital importance to land management. The traditionand belief systemsof the Aborigines show their deep respect of nature and their strong sense of place and belonging. They have a profound spritual connection to the land. They consider land as their mother. So they take responsibility to care for it. They convert land into grass lands for the sake of animals. But non-Aborigines and land owners consider land as something they own for commodity. Kim Scott’s novels paint a vivid picture of the Aboriginal spiritual affinity with nature.This article reviews the inter connectivities between nature and the Aborigines, and their sense of belonging to the land as seen in the novelThat Deadman Dance of the Australian writer Kim Scott.